The influence of plant essential oils on in vitro growth of Pectobacterium and Dickeya spp. bacteria - Małgorzata Schollenberger; Agnieszka Gadomska-Gajadhur; Ewa Mirzwa-Mróz; Damian Kret; Ewa Skutnik; Elżbieta Paduch-Cichal; Mark Gleason (Acta Scientiarum Polonorum: Hortorum Cultus, 2021)
The activity of essential oils from Eucalyptus globulus, Pinus silvestris, Lavandula angustifolia, Juniperus virginiana, Rosmarinus officinalis and Citrus paradise against the soft-rot pathogens Pectobacterium carotovorum subsp. carotovorum, Pectobacterium atrosepticum, Pectobacterium parmentieri and Dickeya solani was determined in vitro. The antibacterial activity of the essential oils will be evaluated using the disk-diffusion method by Kirby-Bauer [Bauer et al. 1966]. It was found that all the presented essential oils varied in antimicrobial activity against the four bacterial strains. No differences in the influence of streptomycin on inhibition of growth of the four bacterial strains were observed. Among six tested plants, essential oils from P. sylvestris had the strongest inhibitory effect on the growth of soft rot bacteria from Pectobacterium genus. This paper constitute the first report on the activity of the essential oils obtained from J. virginiana against soft rot bacteria. They are also the first report on the activity of the essential oils obtained from E. globulus, P. silvestris, L. angustifolia and C. paradisi against P. atrosepticum, P. parmentieri and D. solani as well as on the activity of the R. officinalis essential oils against P. atrosepticum and P. parmentieri.